2002
DOI: 10.1046/j.1440-1827.2002.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p16 and p14ARF is associated with human papillomavirus infection in cervical squamous cell carcinoma and dysplasia

Abstract: The CDKN2 gene encodes two structurally different proteins: a cyclin-dependent kinase inhibitor, p16, which regulates retinoblastoma protein (pRb)-dependent G1 arrest, and a cell cycle inhibitor, p14ARF, which blocks MDM2-induced p53 degradation resulting in an increase in p53 levels that leads to cell cycle arrest. Recent studies have revealed that expression of p16 and p14ARF is influenced markedly by the status of pRb and p53, and p16 overexpression has been demonstrated in cervical neoplasia because of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 39 publications
6
74
0
2
Order By: Relevance
“…INK4a and p14 ARF confirm previous reports that these markers are overexpressed in cervical carcinomas [20][21][22] and are consistent with a compensatory mechanism activated in response to direct interference p53 and pRb by the E6 and E7 HPV oncoproteins.…”
Section: Discussionsupporting
confidence: 90%
“…INK4a and p14 ARF confirm previous reports that these markers are overexpressed in cervical carcinomas [20][21][22] and are consistent with a compensatory mechanism activated in response to direct interference p53 and pRb by the E6 and E7 HPV oncoproteins.…”
Section: Discussionsupporting
confidence: 90%
“…Additional confirmation of E7 expression was provided by the increase in p16 INK4a (Figure 1b), which is correlated to E7 expression (Sano et al, 2002).…”
Section: Waf1supporting
confidence: 53%
“…INK4a has been correlated to E7 expression in cervical cancer samples (Sano et al, 2002). Quercetin treatment lead to a reduction of p16…”
Section: Waf1mentioning
confidence: 99%
“…The inactivation of senescence markers, due to homozygous deletion or hypermethylation of the genes which encode them, may be a significant mechanism in the dysfunction of the Rb and p53 growth regulation pathways during ESCC development (30). However, it has been reported that the senescence pathway remains intact in a large number of prostate cancer and cervical squamous carcinoma cases (31) even if the ki-67 index indicates increased proliferation in these cancers. Zhang et al found that the senescence markers p14 ARF , p15 INK4b , p16…”
Section: ------------------------------------------------------------mentioning
confidence: 99%